Strengthening Pancasila Values Amid Division and the Rise of Disinformation - Zakya, Sarah Maulidya; Ayahan, Hafal Baliq; Azzahra, Inas Fathia Azzahra; Ahmad Bayhaqi; Dewi Sulistianingsih (Universitas Negeri Semarang, 2025)
Pancasila is the foundation of the state as well as the way of life for the Indonesian nation, playing an important role in maintaining the unity and Integrity of the country. In the era of globalization and rapid advancement in information technology, society faces an influx of information that is not always accurate. Disinformation spread through social media not only causes confusion but also has the potential to divide the nation and erode national values. This study aims to re-examine the importance of strengthening Pancasila values amidst the widespread disinformation and the potential for social division. The method used is a literature study with a descriptive qualitative approach through the analysis of various sources such as scientific journals, books, and official documents relevant to the research topic. The results show that Pancasila values, such as humanity, unity, deliberation, and social justice, play a strategic role in shaping critical, tolerant, and wise attitudes in responding to information in the digital era. Through education, family roles, and positive utilization of digital media, Pancasila values can continue to be reinforced as the moral guideline of the nation. This study is expected to contribute to raising public awareness about the importance of Pancasila as a defense against disinformation and in maintaining the unity of Indonesia.